Credit Default of Local Public Sectors in Chinese Government-Pay PPP Projects: Evidence from Ecological Construction - Jie Yang; Lingchuan Song; Zhongdan Xing (Advances in Civil Engineering)
Credit is regarded as a key factor to maintain the sustainability of cooperation between public authorities and social capitals in Government-Pay Public-Private Partnership (PPP) projects. The credit default of local public sectors has become a formidable force to cause termination in several cases. The study aims to explore the critical conditions and main logics behind opportunistic behaviours through literature analysis. In this research, political performance, fiscal illusion, subjective willingness, and objective limitation are identified as four certain conditions. Additionally, the crisp-set Qualitative Comparative Analysis (csQCA) method is applied to determine the connections between conditions and the credit default in the Chinese Government-Pay PPP projects according to 15 cases from the field of ecological construction. Consequently, two combinations with complete sufficiency leading to severe extent of credit default are categorized. The configuration of political performance and fiscal illusion is dominant, thereby causing severe extent of credit default in the preimplementation link. Correspondingly, the configuration of subjective willingness, objective limitation, and nonpolitical performance is crucial in the implementation and postimplementation links. Moreover, fiscal illusion alone could be totally sufficient to lead to a termination. This research not only enriches the theoretical system on credit default of public authorities in Government-Pay PPP projects but also provides reference for all participants to forecast the potential risks especially the credit default in PPP projects.